The social case as a business case: Making sense of social entrepreneurship from an ordonomic perspective - Markus Beckmann (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2009)
This article discusses how the theoretical perspective of ordonomics provides a framework for better understanding and advancing the practice of social entrepreneurship. From an ordonomic perspective, the concept of social entrepreneurship offers a semantic innovation (at the ideas level) whose potential for social innovation can be fully reaped only if it is used as a heuristics for social structural change (on the institutions level). Social entrepreneurs recognize relevant social problems, interpret them as an entrepreneurial challenge, and succeed in turning what was a social case into a business case in a broader sense. Using the real-life example of a successful eco-social entrepreneur, the article demonstrates that such win-win solutions can be reconstructed as the sophisticated management of social dilemmas. It sketches a strategy matrix for the practice of social entrepreneurship and distinguishes four paradigmatic strategies social entrepreneurs can employ to create win-win scenarios by changing the rules of the game to overcome undesirable social dilemmas. The article concludes by discussing social entrepreneurship in the context of new governance processes and highlights key similarities and differences to the concept of corporate citizenship. – – Dieser Artikel nutzt die theoretische Perspektive der Ordonomik, um einen konzeptionellen Beitrag zum Verständnis von Social Entrepreneurship zu entwickeln. Aus ordonomischer Sicht verbindet sich mit dem Konzept von Social Entrepreneurship eine semantische Innovation (auf der Ebene der Ideen), deren Potential für gesellschaftlichen Wandel jedoch daran geknüpft ist, sozialstrukturellen Wandel (also Reformen auf der Ebene der Institutionen) heuristisch anzuleiten. Social Entrepreneurs identifizieren relevante gesellschaftliche Probleme, interpretieren sie als unternehmerische Herausforderungen und vermögen es, einen ,,social case“ in einen ,,business case“ im weiteren Sinne zu transformieren. Am Beispiel eines realen Öko-Sozialunternehmers wird gezeigt, dass derartige Win-Win-Lösungen als das differenzierte Management sozialer Dilemmata rekonstruiert werden können. Der Beitrag entwirft eine Strategiematrix für Social Entrepreneurship und unterscheidet vier paradigmatische Strategien, wie Social Entrepreneurs Win-Win-Potentiale erschließen können, indem sie durch Bindungen unerwünschte soziale Dilemmata überwinden. Abschließend verortet der Artikel das Phänomen Social Entrepreneurship im Kontext von New Governance und diskutiert Unterschiede und Gemeinsamkeiten zum Konzept von Corporate Citizenship.
urn:nbn:de:gbv:3:2-8934
Keywords: D02; D63; L21; M13; M14; 330; Social Entrepreneurship; Ordonomics; Commitments; Strategic Management; Corporate Citizenship; Semantics; Social Structure; Business Ethics; Social Entrepreneurship; Ordonomik; Bindungen; Strategisches Management; Corporate Citizenship; Semantik; Sozialstruktur; Wirtschaftsethik; Unternehmensethik